THE ROLE OF ARTIFICIAL INTELLIGENCE TECHNOLOGY IN TEACHING ENGLISH - Fakhriddin Urinboevich Toshboltaev; Ilmiyaminova Okhistabonu Hamidullo qizi (Ustozlar uchun, 2025)
This article explores the transformative role of Artificial Intelligence (AI) technology in English language teaching. AI has revolutionized language education by enabling adaptive and personalized learning experiences. AI-driven platforms facilitate individualized instruction, allowing learners to receive targeted support based on their specific linguistic needs, cognitive abilities, and areas requiring development.